An Image Encryption Algorithm Based on Chaotic Selection of Robust Cryptographic Primitives - Muhammad, Zahir Muhammad Ziad; Ozkaynak, Fatih (Ieee-Inst Electrical Electronics Engineers Inc, 2020)
With the spread of digital images, the security of these data has become a serious problem. In this study, an image encryption algorithm is designed to ensure the confidentiality of digital images. The original aspect of the proposed algorithm is that it has an architecture that combines unpredictable and random-like features of chaotic systems and cryptographic primitives that have been proven as a result of many years of research. By making use of the advantages of chaotic systems, it has provided the design of an image encryption algorithm that is more resistant to application attacks than mathematical designs. Analysis results and security evaluations have shown that the proposed method can be used successfully in many applications related to security of digital image.
Keywords: Chaos; cryptography; image encryption